Sodium Intake Requirements for Preterm Neonates: Review and Recommendations. Issue 6 (December 2016) - Bischoff, Adrianne R.; Tomlinson, Christopher; Belik, Jaques
Abstract : ABSTRACT: It is widely accepted that sodium is an essential nutritional electrolyte and its deficiency is associated with neurological sequelae and poor growth. The provision of an adequate sodium intake to preterm neonates is hampered by the technical difficulty in clinically assessing total body sodium content. As addressed in this review, there is a lack of consensus on the definition of hyponatremia early in life, but there is no evidence that it should deviate from the widely accepted normative data for adult subjects. A low urinary sodium content is accepted by many as reflecting total body sodium deficiency, yet spot urinary sodium measurements are of questionable clinical value. The hormonal regulation of sodium homeostasis is here reviewed and the mechanism accounting for sodium deficiency–induced growth impairment in preterm infants addressed. Lastly, we provide evidence-based gestational and postnatal age-dependent recommendations for the provision of adequate sodium intake to preterm neonates.